The end all around us apocalyptic texts and popular culture. - Walliss, John, 1974-; Newport, Kenneth G. C. (London ; Oakville : Equinox, 2009)
For centuries the apocalypse has been a recurrent theme within art, literature, music, and more recently cinema. Within the context of contemporary popular culture its influence may be felt in areas as diverse as extreme metal music, disaster movies, anime and manga, Science Fiction dystopianism and the Left Behind series of novels. The aim of this collection of essays is to examine the influence of apocalyptic texts on popular cultural products, focusing on the timelessness and malleability of their themes to audiences. Chapters will focus on the influence of such texts within the areas of fi.
Introduction / John Walliss and Kenneth G.C. Newport -- Songs of fate, hope and oblivion : Bob Dylan's dystopianism and apocalyticism / Gary Baines -- End of the world music : is extreme metal the sound of the apocalypse? / Keith Kahn-Harris -- Babylon's burning : reggae, Rastafari, and millenarianism / Christopher Partridge -- Apocalypse at the millennium / John Walliss -- 'The days are numbered' : the romance of death, doom, and deferral in contemporary apocalypse films / Lee Quinby -- Making things new : regeneration and transcendence in Anime / Mick Broderick -- Selling faith without selling out : reading the Left Behind novels in the context of popular culture / Jennie Chapman -- 'The shadow of the end' : the appeal of apocalypse in literary science fiction / Roslyn Weaver -- An end times virtual 'Ekklesia' : ritual deliberation in participatory media / Robert Glenn Howard -- Index.
Includes bibliographical references and index.
Keywords: Popular culture -- Religious aspects; End of the world; Popular culture -- Religious aspects; Religion; End of the world; Popular culture -- Religious aspects; Populaire cultuur; Einde der tijden; Religieuze aspecten; BODY, MIND & SPIRIT / Gaia & Earth Energies; RELIGION / Christianity / General; RELIGION / Theology; Electronic books